Reconstruction of Bankruptcy Regulations and Suspension of Debt Payment Obligations Based on Islamic Legal Values - Hijratul Pahsyah; Sri Endah; Anis Mashdurohatun (Journal of Social Research, 2023)
The background of this research is that as it happens in the business world, the need for funds is a basic need that must be met by business actors, to overcome the problem of funding needs, capital loans are the solution. The problem that arises is if within the specified time the debtor is unable to pay it. The purpose of this study is to malign  and find that bankruptcy regulations and PKPU have not been based on Islamic justice values, analyze and find weaknesses in current bankruptcy regulations and PKPU, and  analyze and find reconstructions of bankruptcy regulations and PKPU based on Islamic justice values.    In this study, the constructivism paradigm was used. namely the paradigm that is the antithesis of the understanding that lays observation and objectivity in finding a reality or science, This type of research is descriptive analysis, the approach that the author uses is a Sociological Juridical approach,  This research is categorized into doctrinal hukun research (both normative and philosophical juridical), The data analysis method used in this study is qualitative data analysis to obtain descriptive data. This research uses Islamic legal theory as an applied theory, namely the Mashlahah Theory According to Imam Al-Ghazali which is a concept that is used as the main consideration in solving Islamic legal problems because the principle contained in maslahah is the maintenance of the objective purpose of law (maqasid al-shari'ah)  that is, the maintenance of religion, soul, reason, heredity, and property. Based on the results of this study, it was found that the first Bankruptcy Regulation and Suspension of Debt Payment Obligations have not been based on Islamic justice values, especially in article 2 paragraph (1), article 17 paragraph 2 and article 225 paragraph 4, Second, weaknesses were found  in the current bankruptcy and PKPU regulations, including bankruptcy requirements of at least 2 creditors, the temporary decision of PKPU was only given 45 days,  and the fee for curator is too great. For this reason, it is necessary to reconstruct the Bankruptcy Regulation and PKPU, including increasing the bankruptcy requirements for more than 2 creditors, extending the temporary bankruptcy of PKPU for more than 45 days or 1 year, changing the Curator fee calculation system based on agreements with debtors and creditors.